In Search of Peaceful Future of the Asia-Pacific Maritime World: Formulating the Role of Indonesian Navy - Amarulla Octavian (Journal of Maritime Studies and National Integration, 2017)
This article discusses how to formulate the role of Indonesian Navy as an  effort  to  make  peaceful  future  in  the  Asia-Pacific  maritime  world  through  military  history  perspective.  Pacific  War  in  World  War  II  is  perfect  examples  of  how  history  could  not  be  separated  from  the  development  of  any  nation  in  the  world.  No  country  could  establish  itself  as  a  developed  state  without  developing  an  internal  awareness  of its history. It is a record of the nation, either positive or negative, of one  generation  to  be  learned  by  the  next  one.  Although  our  very  existence  is  a  result  of  the  history  of  the  past,  the  path  of  our  future  lies in our hands. It is important for Indonesia’s current generation to excel  positive  contribution  to  the  nation.  This  country  is  currently  facing  complex  challenges,  and  the  policy  and  strategy  we  will  take  would  determine  the  face  of  our  history  in  the  future.  Any  mistakes  in  the  formulation  of  policy  and  strategy  would  eventually  have  negative  implication  to  our country; influencing our future.